IMPLEMENTASI METODE WEIGHTED PRODUCT DALAM MENENTUKAN LEVEL KONDISI PENYANDANG DISABILITAS MENTAL DI JOMBANG - Kurniawan , Rizal; Lazulfa , Indana (Inovate, 2023)
Based on statistical data from the Jombang Regency Central Bureau of Statistics, there are quite a large number of persons with disabilities in Jombang Regency, namely 1,720 people. The Jombang Regency Social Service carries out its duties, namely social rehabilitation for people with disabilities in Jombang Regency. For mental disabilities, care and treatment must be efficient and on target so that several criteria are made that are met to determine the level of severe conditions, mild conditions, or moderate conditions. The criteria measured were reading ability, numeracy ability, writing ability, motoric ability, and verbal thinking ability.With the results of this study it is possible to apply the weighted product method in conducting a decision support system to determine the level of the condition of persons with mental disabilities in Jombang. The system can recommend names of people with disabilities who have the highest recovery rate, from the results of manual calculation analysis and system calculations the results are declared valid. Keywords: Decision Support System, Weighted Product, Condition Level, Mental Disa